Advances in Colloid Science - Muzibur Rahman, Mohammed; Mohamed Asiri, Abdullah (IntechOpen, 2016)
This book Advances in Colloid Science covers a number of up-to-date research advancement and progresses on colloids. It is a promising novel research field that has acknowledged a lot of interest recently. Here, the exciting scientific reports on cutting edge of science and technology associated to facile and economical synthesis, self-assembly, wettability, liquid crystallinity, physical properties, adoptions, morphology, control, drug design, structural properties, and prospective biological and optical implementation of newly designed colloids are concluded. This book presents an overview of recent and current colloidal study of fundamental and significant applications and implementation research worldwide. The colloidal science offers significant new and exciting challenges in biomedical, chemical, physical, and technological field. It is an important booklet for research organizations, governmental research centers, academic libraries, and R&D affianced in recent research and advancement of colloids.